Monitoring for strain-based railway structure assessment approach using optical fibre sensor - Agus Danish Hakim AgosMustaram; Meor Iqram Meor Ahmad; Nur Shufinah Suhaimi; Mohd Zaki Nuawi; Mohd Hafizi Zohari; Ahmad Kamal Ariffin; Aidie Zeid Muhammad Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2024)
Railway transportation is essential and continually evolving with new technologies to achieve high efficiency and passenger safety. Monitoring railways can be challenging, especially when dealing with delicate equipment. This study outlines a basic guideline and real-time monitoring process for railway tracks, serving as precautionary measures. The research employs Fiber Bragg Grating (FBG) sensors directly attached to the railway track’s web surface, which have the potential to cause failures. Before sensor installation, several critical steps were taken to ensure the fragile FBG sensors remained intact. These steps involved preparing sensor arrangements and positioning them before installation. Additionally, a calibration test for FBG is performed using the Universal Tensile Machine (UTM) with a mild steel sample, achieving a measurement of almost 1.2 picometers/micro-strain. As a result, a shift in wavelength was successfully measured and collected, enabling the calculation of strain-stress data for the rail structure during operation. The collected data exhibited no irregularities or anomalies data, indicating the success of the monitoring process. The data obtained from a well-prepared installation greatly differs from that of an underprepared one. This study underscores the necessity of thorough preparation when handling delicate equipment like FBG sensor. Therefore, the FBG sensor has the capability to measure the strain-stress behavior of rail structures, allowing for more accurate predictive assessments to prevent rail failures.